Player perceptions of informal learning in non-educational games - Välisalo Tanja; Vahlo Jukka; Tuuri Kai (United Kingdom, 2025)
The potential of non-educational games in learning is well-established, but there have been relatively few empirical studies attempting to explore the kinds of informal learning take place in non-educational games outside of formal education. Simultaneously, student motivation is known to have a connection to learning outcomes, but there is a lack of research on the relationship between gaming motivations and informal learning in games. This paper aims to fill the gap in research by, firstly, forming an empirically-based understanding of what players perceive they are learning from playing non-educational games, and secondly, exploring the potential connections of self-articulated learning outcomes with motivations to play games and preferences for gameplay activities.
The research data was collected through an online survey panel. The respondents were asked to describe in open-text answers what they had learned by playing games, and their motives and gameplay activity preferences were measured using two psychometric instruments, Motives of the Autonomous Player, MAP (Vahlo and Tuuri, submitted) and the gameplay activity inventory GAIN (Vahlo et al, 2018).
The open-text responses analysed using data-driven content analysis, which resulted in 11 main categories of learning outcomes. Cluster analysis of the main categories revealed three clusters indicating informal game-based learner types: (1) Learning perseverance, learning mainly related to coping skills and self-enhancement, (2) Learning practices and communalities, focusing on practical and interpersonal skills, and (3) Learning to perform, emphasising cognitive and sensori-motor competencies.
Comparisons of the learning outcome clusters with motives and gameplay preferences revealed the learner types had distinct profiles which denote differences between learner types in the overall motivation to play games, in certain motivational factors, and in preferences of gameplay activities. Based on this analysis we suggest the existence of two distinct continuums, transfer of learning, and the situational dependence to gameplay activities, where these learner types are located.
Proceedings of the 16th European Conference on Games Based Learning, ECGBL 2022